2018
DOI: 10.4314/sajas.v48i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing soybean meal with corn gluten meal on milk production and nitrogen efficiency in Holstein cows

Abstract: The objective of the current study was to determine the effects of partial replacement of soybean meal with corn gluten meal on lactation performance and nitrogen (N) efficiency in lactating Holstein dairy cows. Nine multiparous lactating cows in mid lactation (109 ± 19 days in milk) received three treatments in a 3 × 3 Latin square design for 21 days. The three treatments consisted of i) Ctrl: low protein diet with 15.2% crude protein (CP); ii) SBM: soybean meal-based diet with 18.4% CP; and iii) CGM: soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…As a costly and essential ingredient in the diet of dairy cattle, protein supplies ruminal microorganisms with amino acids and nitrogen for the synthesis of microbial protein, and meets the nutritional requirements of the host for various purposes (Liu et al, 2013;Imran et al, 2018). Soybean meal (SBM) is the most common and widely used protein source for the diets of lactating dairy cattle, and it possesses abundant rumen degradable protein (RDP), relatively balanced amino acid profile, and high digestibility of cellulose and pectin (Kwon et al, 2011;Imran et al, 2018). It has been verified that supplementing SBM resulted in the increments in dry matter intake, milk production, and milk protein concentration of grazing Holstein cows with ad libitum access to grass silage (Rego et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a costly and essential ingredient in the diet of dairy cattle, protein supplies ruminal microorganisms with amino acids and nitrogen for the synthesis of microbial protein, and meets the nutritional requirements of the host for various purposes (Liu et al, 2013;Imran et al, 2018). Soybean meal (SBM) is the most common and widely used protein source for the diets of lactating dairy cattle, and it possesses abundant rumen degradable protein (RDP), relatively balanced amino acid profile, and high digestibility of cellulose and pectin (Kwon et al, 2011;Imran et al, 2018). It has been verified that supplementing SBM resulted in the increments in dry matter intake, milk production, and milk protein concentration of grazing Holstein cows with ad libitum access to grass silage (Rego et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, SBM also has its own significant disadvantages, including low levels of rumen undegradable protein (RUP), low ratio of methionine (Met) to lysine (Lys), and the presence of multiple anti-nutritional agents (e.g., trypsin inhibitors, hemagglutinins, raffinose, and stachyose) (Yoo et al, 2009;Zhang et al, 2013;Imran et al, 2018). Fermentation could be an effective approach to promote the quality of SBM via microbial metabolism or microbial enzymatic activity (Chatterjee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Protein is an indispensable component in the ration for dairy cows, it offers rumen microbe nitrogen and amino acids to synthesize the microbial protein, as well as meets the nutritional demands for diverse metabolisms of the animal (1,2). As the most commonly adopted protein source for dairy cattle, soybean meal milk (SBM) could be characterized by its well-balanced amino acid profile, bountiful rumen degradable protein (RDP) amount, and high digestibility of cellulose and pectin (1,3). Rego et al (4) reported that dietary inclusion of SBM enhanced the dry matter intake, milk yield, and milk protein production of grazing dairy cattle having ad libitum access to grass silage.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the nutritional drawbacks of SBM have also been noticed, which are mainly reflected by the low rumen undegradable protein (RUP) content and the existence of various anti-nutritional factors (e.g., trypsin inhibitors, haemagglutinins, raffinose, and stachyose) (1,5,6). The promotion of the overall quality of SBM can be achieved via the microbial fermentation process (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation